Sobre la constitución del saber administrativo. - Román, Juan Pablo (Revista Economia & Gestão, 2009)
This paper questions how management has been constituted. On the one hand discussing its status – is it theoretical, ideological or doctrinal knowledge? On the other hand, commenting the excesses on the application of some concepts and techniques, coming from social sciences. Therefore, it tries to enhance a conscious approach, from both academics and practitioners, to the management discipline. The latter regarding the settlement of any management model within a new context.